2014
DOI: 10.1111/hepr.12312
|View full text |Cite
|
Sign up to set email alerts
|

Integrins αvβ6, α6β4 and α3β1 are down‐regulated in cholangiolocellular carcinoma but not cholangiocarcinoma

Abstract: Our results first indicated downregulation of αvβ6, α6β4 and α3β1 integrins in CoCC, in contrast to its high expression in CCC, suggesting a diagnostic value of integrins in the differential diagnosis of CoCC and CCC, as well as a useful inducible marker of the intermediate features of CoCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Soejima et al indicated the downregulation of αvβ6, α6β4 and α3β1 integrins in CoCC and its respectively high expression in CCC. These findings suggest the use of integrins as a diagnostic tool in the differential diagnosis of CoCC and CCC [13]. These findings are also supported by earlier studies demonstrating that αvβ6 integrin is a promising marker of CCC, but not HCC as the expression levels were very different in these tumors [14].…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Soejima et al indicated the downregulation of αvβ6, α6β4 and α3β1 integrins in CoCC and its respectively high expression in CCC. These findings suggest the use of integrins as a diagnostic tool in the differential diagnosis of CoCC and CCC [13]. These findings are also supported by earlier studies demonstrating that αvβ6 integrin is a promising marker of CCC, but not HCC as the expression levels were very different in these tumors [14].…”
supporting
confidence: 81%
“…In this study, Soejima et al evaluated integrin expression and immunolocalization of the extracellular matrix proteins in cholangiolocellular carcinoma (CoCC), CCC, hepatocellular carcinoma (HCC) and classical type combined hepatocellular CCCs. Samples were collected and immunostained for β6, β4 and α3 integrins, fibronectin and laminin [13]. Little or no positivity for β6, β4 and α3 integrins were shown in the CoCC and HCC specimens.…”
mentioning
confidence: 99%
“…The genes that were simultaneously presented in the extracellular matrix-receptor pathway and were revealed to be ASGs, included chondroadherin (CHAD), integrin subunit (ITG)-A3, ITG-B1 and laminin subunit alpha-5 (LAMA5). Three of the aforementioned genes, (ITGA3, ITGB1 and LAMA5) have previously been demonstrated to be associated with the progression of ICC (25,26). CHAD encodes a cartilage matrix protein, which may mediate adhesion of isolated chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin a1b1 has been shown to be involved in the attachment to collagen IV and laminins containing the a4 subunit, 30,60 while a3b1, a6b1, and a6b4 have all been shown to interact specifically with laminins. [60][61][62] aVb5, aVb1, and a5b1 along with several other integrin heterodimers have been shown to interact with RGD sequences from varying ECM proteins, including collagen I, fibronectin, and vitronectin. 30,35,63 The increase of each of these subunits in adipogenically differentiated cultures, along with increases in ECM proteins that they are able to interact with, supports the hypothesis that these integrins may be important to the differentiation process.…”
Section: Discussionmentioning
confidence: 99%